KETERAMPILAN METAKOGNITIF DAN BERPIKIR TINGKAT TINGGI DALAM PEMBELAJARAN GENETIKA (ARTIKULASI KONSEP DAN VERIFIKASI EMPIRIS) - Sumampouw, Herry Maurits (BIOEDUKASI, 2011)
ABSTRACT- Metacognition skill is regarded as higher order thinking. It is important to assure the success of achieving particular learning goal as it guarantees the improvement of student?s ability iof thinking towards particular given concept. Building metacognition skill has been commonly used in learning Genetics. One example of method within metacognition is Reading, Questioning and Answering (RQA model. Theoritically, this model is able to facilitate student to improve his higher order thinking and therefore, metacognition skill in Genetics can be raised through this model. Keywords: Metacognition skill, higher order thinking